Bank service quality and its relationship towards customer satisfaction and loyalty: a case study on Agrobank’s 3F loan/ Vincent Mambu - Mambu, Vincent (2011)
This study attempts to determine the factors of bank service quality towards customer satisfaction and customer loyalty for Agrobank’s 3F loan. The measurement used is in accordance with the model conceptualized by Yavas and Arsan (1995). The twenty (20) items of bank service quality relevant to the banking sector are distributed across four (4) dimensions: service environment; interaction quality; empathy and reliability, four (4) items on customer satisfaction and two (2) items on customer loyalty. The respondents will have to decide based on Likert-type five point scale for measuring the Bank service quality dimensions, customer satisfaction and loyalty. The data were collected and administered by means ofstructured questionnaires on twenty (20) items. There were one hundred and thirty (130) usable, completed returned questionnaires for analysis using SPSS Version 17 software.